PERTANGGUNGJAWABAN PIDANA DALAM TINDAK PIDANA KORUPSI PENGADAAN BARANG DAN JASA DI LINGKUNGAN PEMERINTAHAN - Bulqis Bulqis (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
Corruption in government procurement of goods and services remains one of the principal sources of state financial leakage in Indonesia, as reflected in data from the Corruption Eradication Commission indicating that nearly ninety percent of cases adjudicated in 2024 were directly connected to the procurement sector (Komisi Pemberantasan Korupsi, 2024). This article aims to analyze the juridical construction of criminal liability for perpetrators of procurement corruption, encompassing public officials, providers of goods and services, and corporations, while also identifying the structural obstacles that impede effective enforcement. The research employs a normative juridical method combining a statutory approach, a conceptual approach, and a case approach toward relevant corruption court decisions. The findings indicate that although the legal framework under Law Number 31 of 1999 in conjunction with Law Number 20 of 2001 and the 2023 National Penal Code has accommodated three models of criminal liability, namely individual fault, vicarious liability, and the corporate identification doctrine, their application in practice remains skewed, as enforcement is disproportionately directed at individual perpetrators rather than corporations that equally benefit from the offense. The definitional gap concerning corporations between the new Penal Code and the Anti-Corruption Law further generates legal uncertainty in determining the proper subject of liability in complex procurement cases. This article offers a novel contribution in the form of an integrated analytical framework linking procurement stages, prevailing modi operandi at each stage, and the most relevant model of criminal liability to be applied, an approach that has not been systematically explored in prior specialized criminal law literature. The study recommends harmonizing corporate definitions across regulations, strengthening evidence gathering through investigative audits and digital forensics, and reorienting penal policy toward asset recovery as the primary objective of enforcement against procurement corruption in the government sector. Keywords: Criminal Liability; Corruption; Procurement Of Goods And Services; Corporation; State Financial Loss